Following Jatropha from Bandung to Sumbawa: Entanglement between University and Industry in Practice. Issue 1 (1st March 2017) - Fatimah, Yuti A.
Abstract : This article contributes to understanding innovation in an emerging economy by building on the STS concept of entanglement and collaboration. Specifically, it develops an analytical framework to capture the duality of innovation actors in creating novelties and in maintaining regularities of the existing economic and political contexts. Entanglement is characterized by the emergence of new associations that allow the actors to innovate, while collaboration is characterized by the presence of new activities to maintain the existing economic and political contexts. This article demonstrates that the transformation of Jatropha-based fuel from invention to commercial transaction was facilitated by a series of incremental collaborations, which lasted different amounts of time depending on the context. The article suggests that the local institutional context plays a crucial role in allowing actors to take autonomous actions to pursue biofuel innovation. However, when their strategy encounters an unfavorable socioeconomic environment due to political change at the national level, their ability to accomplish their economic goals through new innovation declines.